Nomenclature, taxonomy, and conservation of the neotropical genus Sphyrospermum (Ericaceae: Vaccinieae), including five new species for Colombia, Ecuador, and Peru - Luteyn, James L.; Pedraza-Peñalosa, Paola (Phytotaxa, 2013)
Nomenclature, taxonomy, and conservation of the neotropical genus Sphyrospermum (Ericaceae: Vaccinieae), including five new species for Colombia, Ecuador, and Peru